Simplifying Capacitive Sensor Readout Using a New Direct Interface Circuit - Hidalgo-López, José Antonio; Castellanos-Ramos, Julián (IEEE, 2022)
Direct interface circuits (DICs) are efficient for reading resistive, capacitive, or inductive sensors in a digital format. The simplest DICs consist of just a few passive elements that connect a digital processor (DP) to a sensor. When reading capacitive sensors, one or several calibration capacitors and/or several charging and discharging cycles are needed to make the estimation, and the result usually requires complex arithmetic operations. This article presents a new type of capacitive DIC that is simple in terms of hardware, needing only two resistors of known value and the DP in order to make the capacitance estimation. In addition, the reading method requires a single sensor charging and discharging cycle, which reduces acquisition time and power consumption. Two time measurements are taken during the discharge, which, through a linear transformation of their subtraction (using two constants stored in the DP), give the value of the capacitance. These arithmetic operations are easily implemented on any DP and consume fewer resources than the divisions required on other capacitive DICs. The design has been tested for a wide range of capacitances (from 100 pF to 561 nF), including the value of several capacitive sensors. The average relative error for the entire range is 0.41%, the linearity errors are below 0.3%, and the minimum signal-to-noise ratio (SNR) value is 64 dB.
Keywords: Tacto; Detectores; Capacitance to digital; Capacitive sensors; Direct interface circuits (DICs)